Observasi Penerapan Nilai-nilai Pancasila di SMAS YPM 2 Sukodono - Robby Andyka Pratama (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The application of Pancasila values in the educational environment is important, but most of the younger generation still lacks the awareness to be able to apply the values of Pancasila. This research aimed at analyzing the implementation of the Pancasila values at SMAS YPM 2 Sukodono with a focus on learning activities and daily interactions between teachers, students, and all elements of the school. Observations were conducted using descriptive qualitative research methods with participatory observation data collection techniques. The result of observation shows a high level of application of Pancasila value and the highest percentage is in the implementation of the fourth precept of the Pancasila (93%) related to the implementation of deliberation and respect for opinions in decision making, while the application of the fifth precept shows the lowest percentage (87%) which is reflected in the lack of student awareness in maintaining environmental cleanliness and obedience to school rules. The results showed that the Pancasila principles have been well implemented in the school. Hopefully, with this research, the younger generation will begin to grow awareness to be able to apply the Pancasila values so that it can produce a younger generation of character and integrity.